Telegram bot: Building technology IV (DBT244) / Mohamad Ezad Hafez Mohd Pahroraji ... [et al.] - Mohd Pahroraji, Mohamad Ezad Hafez; Husin, Azamuddin; Ismail, Asmat; Wan Zaharuddin, Wan Akmal Zahri; Abdullah, Mohd Rofdzi (2024)
UiTM lecturers have a critical responsibility: imparting knowledge to students. However, managing teaching materials, including lecture notes in various file formats, can be challenging. These notes often end up scattered across hard drives, cloud storage, and USB drives, leading to confusion and forgetfulness. Additionally, ensuring that all students receive updated files can be cumbersome. To address these issues, a Telegram Bot was developed. Operating within the popular messaging app Telegram, this bot offers several advantages. First, it provides centralized access, allowing lecturers to retrieve teaching materials anytime and anywhere without the need for additional app installations. Second, instead of carrying a laptop to connect to projectors, lecturers can use their mobile phones. By wirelessly connecting to projectors using a wireless display receiver, they can display teaching materials directly from the Telegram Bot. Finally, the bot allows for real-time updates to lecture notes, ensuring that students always have access to the latest versions. In summary, this innovative solution streamlines lecturers’ tasks, enhances accessibility, and simplifies the teaching process.